Surgical tactics in hepaticocholedochus strictures - Ainara Darbayeva; Ibragim Tashev; Zhaksylyk Doskaliyev; Aliya Taganova (National Scientific Medical Center, 2016)
Cicatricial strictures of the bile ducts are complications of the diseases or damage during surgery on the hepatobiliary system. Rarely scar strictures are inflammatory in nature or are the results of primary sclerotic cholangitis. However, in 95 - 97,4 % cases disease is caused by iatrogenic damage of bile ducts - improper drainage or untidy surgical manipulations on bile ducts during the cholecystectomy. Present work is based on experience of surgery of 52 patients with strictures of hepaticocholedochus, who underwent treatment at Surgery Department of National Scientific Research Medical Center JSC during the 2002-2013.